Raw material management for frozen Parupeneus heptacanthus fillet products at PT BARUNA, Lamongan, East Java - Larasati, Melani (Generasi Biologi Indonesia, 2024)
One of the processing methods for whiskered goatfish (Parupeneus heptacanthus) is converting it into frozen fillet products. The raw material management for the production of whiskered goatfish fillet includes receiving the raw materials, washing, filleting, trimming, deboning, and sizing. The aim of this article is to explore the raw material management process in the production of whiskered goatfish fillet at PT Bahari Biru Nusantara. A descriptive method was employed, utilizing both primary and secondary data sources. Data collection was conducted through observation, interviews, active participation, and literature review. Inventory planning and raw material receiving scheduling at PT Bahari Biru Nusantara are crucial to address demand fluctuations and maintain smooth production. Consideration of environmental factors such as seasonality, weather, climate, and resource sustainability also plays a role in inventory management strategies.